Optimalisasi Pola Hidup Sehat pada Masyarakat di Kelurahan Legok Kota Jambi - Fithriyani, Fithriyani; M, Rino (Jurnal Abdimas Kesehatan (JAK), 2024)
Improving the degree of public health can be started by increasing sufficient knowledge about healthy lifestyles. A disease can be identified by a medical examination, not only providing education. This community service activity aims to increase public understanding of the importance of health and maintaining a healthy lifestyle. This activity was on November 4, 2022 at RT 39 house, Legok Village, Jambi City. Method of implementation of activities in the form of education about healthy lifestyles. Education provided in the form of providing material through lectures and discussions, media used powerpoint and leaflets. The output target to be achieved is to achieve changes in the behavior of individuals, families and communities in fostering and maintaining healthy living behaviors and healthy environments, as well as playing an active role in efforts to realize optimal health degrees. This activity was attended by 22 people from Rt 39 Legok Village, cadres and heads of RT along with professional students of Ners. The results of this activity increase people's understanding of healthy lifestyles and apply them in daily life